The association of positive mental health indicators and normal body weight, Belgian HIS 2018. (30th September 2020) - De Ridder, K; Drieskens, S; Demarest, S
Abstract: Background: An important health promotion goal is to maintain a normal body weight. However, knowledge about positive mental health indicators that might be associated with normal weight is scarce. The aim is to study positive mental health indicators and normal weight in a cross-sectional national representative population sample. Methods: Study participants included adults aged ≥ 18 year (n = 6643) of the Belgian Health Interview Survey (HIS) 2018. Mental health indicators were having no psychological distress (GHQ-12<2), no self-reported anxiety or depression (EQ_5D), medium to high vitality (SF-36 vitality scale) and high to medium level of life satisfaction. BMI was calculated on self-declared height and weight. The associations were assessed through logistic regression taking into account confounding and effect modification by age, gender, educational level, health status, physical activity, daily eating of fruit and vegetables and daily consuming sugared soft drinks or sweet/salty snacks. Results: 50.1% had a BMI≥25. In the crude models, all indicators were negatively associated with being obese, but there was no association between having a normal weight (versus overweight and obesity) and absence of psychological distress, absence of anxiety and depression, and medium to high vitality. Medium to high level of life satisfaction was associated with normal weight in the fully adjusted model (OR 1.3; 95%CI 1.0-1.6) but when stratified, medium to high life satisfaction was associated with normal weight only among high educated women (OR 1.8; 95%CI 1.1-2.9), but not among men and low educated women. Surprisingly, among low educated women, having no psychological distress was negatively associated with normal weight (OR 0.7; 95%CI 0.5-0.9). Conclusions: These preliminary results showed a variable impact of gender and educational levels on the association between positive mental health indicators and normal weight. Trends and distribution in society should be further explored. Key messages: Although unequivocal associations with obesity, positive mental health is not clearly associated with normal body weight in today's obesogenic society. The effect of a shift towards a higher BMI in society on mental health needs to be further explored.